Method for microwave solid-phase tackifying of polyamide, product and application
By combining microwave radiation with chain extenders to solid-state polyamide, the problems of long production cycle and high energy consumption in solid-state polycondensation were solved, resulting in a significant increase in polyamide viscosity and improved production efficiency.
Patent Information
- Application Number
- CN202410657982.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2025-11-25
AI Technical Summary
In existing technologies, the solid-phase polycondensation method for polyamide has a long production cycle and high energy consumption. Furthermore, traditional methods cannot effectively increase the molecular weight and viscosity of polyamide, leading to a decline in product performance.
A microwave-irradiated solid-phase polyamide method was adopted, in combination with chain extenders such as maleamic acid copolymer and maleimide copolymer. The thickening reaction was carried out in the solid-phase polycondensation raw material by microwave irradiation, and the temperature and time were controlled to increase the relative viscosity of the polyamide.
After microwave irradiation for no less than 30 minutes, the relative viscosity of polyamide increased by no less than 0.2, which significantly improved the viscosity of polyamide, shortened the production cycle and reduced energy consumption.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, and relates to a method, product and application of microwave solid-phase thickening polyamide. Background Technology
[0002] In the melt polycondensation process of polyamide, as the melt viscosity increases, the escape of small molecules, the stirring of the melt, and the discharge become very difficult. Furthermore, the aggravation of side reactions leads to a decline in product performance. Studies have shown that microwave radiation can be used in the solution polymerization or melt polycondensation of polymers such as polyimide. Compared with traditional synthesis methods, the synthesis time is significantly shortened and the yield is increased. However, even with microwave radiation polycondensation, the original drawbacks of solution polymerization or melt polycondensation methods cannot be avoided.
[0003] Therefore, melt polycondensation cannot achieve the production of high-viscosity polyamides. For the demand of linear high-molecular-weight polyamides, solid-phase polycondensation is widely used in industry. Solid-phase polycondensation of polyamides is a polycondensation reaction that occurs in a solid state. A polyamide prepolymer with a certain molecular weight is heated to approximately 10–40°C above its glass transition temperature and below its melting point. Vacuuming or purging with an inert gas provides gas protection while removing small-molecule products, allowing the polycondensation reaction to continue. The essence of solid-phase polycondensation lies in the reaction between end-group functional groups. Because the solid is not melted, the large molecular chains of polyamide cannot move, but the end groups can diffuse in the amorphous region. When reactive end groups (such as the terminal carboxyl and amino groups of polyamide) diffuse and approach each other, effective collisions occur, resulting in a polycondensation reaction. Therefore, solid-phase polycondensation can increase molecular weight while inhibiting degradation reactions and the formation of byproducts, ensuring product quality. However, in industrial production, when solid-phase polycondensation is used to increase the molecular weight of polyamide, the production cycle is too long, and the process cost and energy consumption are high. After the polyamide is produced by melting, it is often necessary to wash it with water to remove small molecule impurities and oligomers, and then continue to purge with nitrogen and dry it at high temperature, which also requires a long production cycle and high energy consumption. Summary of the Invention
[0004] To address the above problems, this invention provides a method, product, and application for solid-phase thickening of polyamides. By employing microwave irradiation of solid-phase polyamides and optionally a chain extender, solid-phase thickening of polyamides is achieved through a simple method. After microwave irradiation for at least 30 minutes, the relative viscosity increase of the polyamide is not less than 0.2. Through further research, the inventors of this invention have unexpectedly discovered that the thickening effect of the microwave irradiation method for solid-phase polyamides of this invention is particularly significant when the chain extender is at least one of maleamic acid copolymers and maleimide copolymers, more preferably maleimide copolymers.
[0005] The first aspect of the present invention is to provide a method for microwave solid-phase tackifying polyamide, comprising placing a solid-phase polycondensation raw material, including a polyamide and an optional chain extender, in a sealable container, and subjecting the solid-phase polycondensation raw material to microwave irradiation under a protective atmosphere or low-pressure environment and under mixing conditions to obtain a tackifying polyamide; wherein, during the microwave irradiation process, the solid-phase polycondensation raw material is kept at a temperature between its crystallization temperature and its melting temperature for at least 30 minutes.
[0006] According to some preferred embodiments of the present invention, the microwave irradiation includes three stages: a rapid heating stage, a slow heating stage, and a holding stage; preferably, in the rapid heating stage, the heating rate is 1 to 50°C / min, in the slow heating stage, the heating rate is 1 to 20°C / min, and in the holding stage, the temperature range is within ±10°C of a preset value.
[0007] According to some preferred embodiments of the present invention, the microwave power of the microwave field is 80W to 5000W, for example 80W, 150W, 200W, 250W, 350W, 450W, 550W, 750W, 1000W, 2000W, 3000W, 5000W, and any two values or any range of any two values, preferably 200-1000W.
[0008] According to the present invention, during microwave irradiation, the solid-phase polycondensation raw material is kept at a temperature between the crystallization temperature and the melting temperature for more than 30 minutes, preferably between 30 minutes and 24 hours, for example 30 minutes, 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 15 hours, 20 hours, 24 hours, and any two values or any range of any two values.
[0009] According to some preferred embodiments of the present invention, the polyamide is a solid particle or powder.
[0010] According to some preferred embodiments of the present invention, the protective atmosphere is nitrogen and / or an inert gas.
[0011] According to some preferred embodiments of the present invention, the low-pressure environment is preferably achieved by a vacuum pump.
[0012] According to some preferred embodiments of the present invention, the polyamide is stirred during the microwave irradiation process, and the stirring method is one or a combination of mechanical stirring, magnetic stirring or inert gas stirring.
[0013] According to some preferred embodiments of the present invention, after microwave irradiation, the increase in the relative viscosity of the tackifying polyamide to that of the polyamide is not less than 0.2.
[0014] As an example, polyamide or a composition containing polyamide and chain extender is placed in a sealable container, which is mounted in a microwave device equipped with a stirring device and temperature control. A protective gas is introduced into the sealable container or the interior of the sealable container is kept in a low-pressure environment. While stirring the solid-phase polycondensation raw material containing polyamide and chain extender, a microwave field is applied to the sealable container. The solid-phase polycondensation raw material is kept at a temperature between the crystallization temperature and the melting temperature for more than 30 minutes, thereby achieving solid-phase thickening of polyamide.
[0015] Preferably, the sealable container is equipped with a stirring device to facilitate temperature uniformity within the container. For easier monitoring of microwave conditions, the microwave irradiation equipment is preferably equipped with a temperature detection and control device.
[0016] The stirring device is preferably a mechanical stirring paddle, and the mechanical stirring paddle is preferably made of a material that does not absorb microwaves, such as polytetrafluoroethylene.
[0017] According to some preferred embodiments of the present invention, the polyamide is selected from at least one of polyamide-6, polyamide-66, copolymer of polyamide-6 / polyamide-66, polyamide-1010, polyamide-610, polyamide-612, polyamide-11, polyamide-12, polyamide-46, polyamide-6T, aromatic polyamide, and elastic polyamide.
[0018] According to some preferred embodiments of the present invention, when the solid-phase polycondensation raw material contains a chain extender, the mass ratio of the polyamide to the chain extender is 100:(0.1-20), preferably 100:(0.3-10), for example, 100 to 0.3, 0.5, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, and any two values or any range of any two values; more preferably 100:(0.3-3).
[0019] According to some preferred embodiments of the present invention, the chain extender is selected from at least one of the following: epoxy functionalized chain extender, oxazoline chain extender, carbonate functionalized chain extender, epoxy chain extender, bicyclic chain extender, isocyanate chain extender, phosphorus-containing chain extender, maleic anhydride copolymer, maleamic acid copolymer, and maleimide copolymer; preferably, the chain extender is selected from at least one of maleamic acid copolymer and maleimide copolymer, and more preferably, the chain extender is a maleimide copolymer.
[0020] When the solid-phase polycondensation raw material contains a chain extender, it can be a direct mixture of polyamide and the chain extender, or a composition obtained by melt blending a direct mixture of polyamide and the chain extender using a rubber-plastic blending equipment. The melt blending method can be any thermoplastic melt blending processing method in the prior art, preferably screw extrusion, internal mixing, open milling, or continuous mixing, and more preferably screw extrusion. The rubber-plastic blending equipment used can be an open mill, internal mixer, single-screw extruder, twin-screw extruder, or torque rheometer, etc. The materials can be pre-mixed using a mixing device, selected from existing high-speed mixers, kneaders, and other mechanical mixing equipment.
[0021] According to the present invention, the maleamic acid copolymer and the maleimide copolymer are each carbon chain polymers, wherein heteroatoms O and N are present in the side groups.
[0022] For example, the maleic anhydride group refers to The maleimide group refers to Maleamide group refers to
[0023] According to some preferred embodiments of the present invention, the content of acid anhydride in the maleamic acid copolymer and the maleimide copolymer is not higher than 50%, preferably not higher than 30%, based on the total molar amount of structural units containing acid anhydride groups, maleamide groups, maleamic acid groups and maleimide groups as 100%.
[0024] According to some preferred embodiments of the present invention, the maleamic acid copolymer and the maleimide copolymer are each microspheres, preferably, the average particle size of the microspheres is 0.2 to 100 micrometers.
[0025] According to some preferred embodiments of the present invention, the maleamic acid copolymer and the maleimide copolymer are each products of the amidation or imidation of maleic anhydride and its derivative copolymers; more preferably,
[0026] When the maleic anhydride and its derivative copolymers are prepared by amidation, the step of reacting the maleic anhydride and its derivative copolymers with ammonia or ammonia water is included.
[0027] When preparing the maleiminated copolymer by imidization of maleic anhydride and its derivative copolymers, the process includes the steps of first reacting maleic anhydride and its derivative copolymers with ammonia or ammonia water, and then heating to obtain the imidized product.
[0028] More preferably, when the maleamic acid copolymer and the maleimide copolymer are each prepared by ammonia, the maleamic acid copolymer and the maleimide copolymer are each microspheres with an average particle size of 0.2 to 10 micrometers, preferably 0.3 to 3 micrometers, more preferably 0.4 to 2 micrometers; and / or,
[0029] More preferably, when the maleamic acid copolymer and the maleimide copolymer are each prepared by ammonia water, the preparation includes spray drying after reaction with ammonia water. Preferably, the maleamic acid copolymer and the maleimide copolymer are each microspheres with an average particle size of 0.2 to 100 micrometers, preferably 2 to 60 micrometers, and more preferably 5 to 50 micrometers.
[0030] According to some preferred embodiments of the present invention, when the maleamic acid copolymer and the maleimide copolymer are each microspheres, preferably, the average particle size of the microspheres is 0.2 to 100 micrometers, more preferably 0.2 to 60 micrometers, more preferably 0.3 to 3 micrometers, even more preferably 0.4 to 2 micrometers, or more preferably 5 to 50 micrometers.
[0031] According to some preferred embodiments of the present invention, the maleic anhydride and its derivative copolymers are copolymers containing one or more of the structural units of maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt groups; more preferably,
[0032] Maleic anhydride and its derivative copolymers are copolymers of polymeric monomers containing one or more of the following groups: maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt, and monomers containing isolated carbon-carbon double bonds.
[0033] According to some preferred embodiments of the present invention, the maleamic acid copolymer and the maleimide copolymer are each products of the amidation or imidization of maleic anhydride copolymers; more preferably,
[0034] The maleic anhydride copolymer is a linear copolymer of maleic anhydride and a monomer containing isolated carbon-carbon double bonds; more preferably,
[0035] The maleic anhydride copolymer is at least one of a binary copolymer and a ternary copolymer; further, even more preferably,
[0036] The binary copolymer is a copolymer of maleic anhydride and one or more selected from butene, isobutene, cis-butadiene, pentene, isoprene, cyclopentadiene, dicyclopentadiene, hexene, hexadiene, cyclohexadiene, octene, octadiene, cyclooctadiene, styrene and its derivatives, and vinyl alkyl ethers. More preferably, the molar content of the structural unit provided by maleic anhydride in the binary copolymer is 10% to 90%, preferably 20% to 80%, and more preferably 30% to 70%.
[0037] The styrene and its derivatives include, but are not limited to, one or more of hyperbranched styrene, sulfonated styrene, and α-methylstyrene.
[0038] More preferably, the terpolymer is a copolymer of maleic anhydride, styrene, and isobutylene. More preferably, the molar content of the structural unit provided by maleic anhydride in the terpolymer is 47%-52%, preferably 48%-51%, and the molar ratio of the structural unit provided by isobutylene to the structural unit provided by styrene is 1:0.2-7.5, more preferably 1:1-5.
[0039] According to some preferred embodiments of the present invention, the maleic anhydride copolymer is a linear alternating copolymer of monomers containing isolated carbon-carbon double bonds as described above.
[0040] According to some preferred embodiments of the present invention, the maleic anhydride copolymer is a copolymer microsphere, more preferably a copolymer microsphere prepared by a self-stabilizing precipitation polymerization method, and preferably the particle size of the copolymer microsphere is 0.2 to 10 micrometers, more preferably 0.3 to 3 micrometers, and more preferably 0.4 to 2 micrometers.
[0041] The maleic anhydride copolymer microspheres can be obtained commercially or prepared using existing methods, including but not limited to the methods used for the raw materials in the embodiments of this invention.
[0042] When the maleic anhydride copolymer reacts with ammonia, the reaction of the maleic anhydride copolymer with ammonia can be referred to CN 112574336 A.
[0043] When the maleic anhydride copolymer reacts with ammonia, CN112852356A can be consulted, and the technique for heating imidization can be consulted CN 112574336 A.
[0044] According to some preferred embodiments of the present invention, and for the purpose of explaining the invention more specifically:
[0045] The maleic anhydride copolymer is a product prepared by fully or partially imidizing the anhydride groups contained in the maleic anhydride copolymer; preferably, the imidization modification method includes the steps of reacting the maleic anhydride copolymer with ammonia water or ammonia gas, and then heating to obtain the imidized product; preferably,
[0046] The maleic anhydride copolymer is mixed with ammonia and reacted, then spray-dried, and then heated at 175-230°C, preferably 178-210°C; or the maleic anhydride copolymer is reacted with ammonia and then heated at 175-230°C, preferably 178-210°C.
[0047] According to some preferred embodiments of the present invention, the maleic anhydride copolymer is a product of the maleic anhydride copolymer containing anhydride groups after complete or partial amidation modification; preferably, the amidation modification method includes: reacting the maleic anhydride copolymer with ammonia water or ammonia gas to obtain the amidation modified product; more preferably, the maleic anhydride copolymer is mixed with ammonia water and then spray-dried to obtain amidation modified copolymer microspheres.
[0048] A second aspect of the present invention is to provide a product obtained by the method described in the first aspect. The product of the present invention has a significantly increased relative viscosity compared to polyamides of the same composition, with an increase of 0.2 or more.
[0049] A third aspect of the present invention is to provide the application of the method described in the first aspect or the product described in the second aspect in solid-phase thickening and articles.
[0050] The microwave solid-phase thickening method for polyamide described in this invention can be applied to the industrial solid-phase thickening of polyamide. It has the advantages of simple equipment, high efficiency and low energy consumption. While achieving solid-phase thickening effect, it can also effectively remove moisture, volatile impurities, small molecule products, low molecular weight polyamide, unreacted monomers, etc. from solid polyamide, thereby improving the quality of polyamide products.
[0051] The advantages of this invention are:
[0052] This invention provides a method, product, and application for solid-phase thickening of polyamides. By employing microwave irradiation of solid-phase polyamides and optionally a chain extender, solid-phase thickening of polyamides is achieved through a simple method. After microwave irradiation for at least 30 minutes, the relative viscosity increase of the polyamide is not less than 0.2. Through further research, the inventors unexpectedly discovered that the thickening effect of the microwave irradiation method for solid-phase polyamides of this invention is particularly significant when the chain extender is at least one of maleamic acid copolymers and maleimide copolymers, more preferably maleimide copolymers.
[0053] The inventors believe that the reason why this invention has the above advantages may be due to the following:
[0054] The strongly polar groups of polyamides, including amide groups, ester groups, terminal carboxyl groups, and terminal amino groups, can absorb microwave radiation and rapidly heat up in microwaves, increasing the collision probability of active end groups in the amorphous region of the solid-phase polyamide. Furthermore, the polar end groups themselves can absorb microwaves and quickly reach the activation energy for the reactive polycondensation reaction. On the other hand, byproducts such as moisture, volatile components, monomers, and oligomers in the solid-phase polyamide are more easily extracted, avoiding processes such as water washing and high-temperature inert gas purging in industrial production. This invention can improve the efficiency of solid-phase polycondensation processes in existing industrial technologies, shorten the production cycle, and reduce energy and water consumption. The reaction mechanism of maleamic acid copolymers for thickening nylon requires further investigation. Theoretically, carboxylic acids can react with the terminal amino groups of nylon, and amide groups can react with the terminal carboxyl groups of nylon, forming a chain extender that reacts with both groups in nylon simultaneously through amidation. The reason for the thickening effect of maleimide copolymer on nylon: The reaction mechanism needs further study. The thickening effect of nylon is an unexpected discovery. It may be that the imide groups in the imide copolymer and the amide groups in the nylon underwent an amide exchange reaction.
[0055] The present invention will now be explained in detail with reference to the embodiments. Detailed Implementation
[0056] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0057] Unless otherwise specified, the raw materials used in the following examples are all commercially available products.
[0058] The copolymer of polyamide 6 / 66 has a relative viscosity of 2.0, sourced from Sinopec Nanjing Chemical Research Institute Co., Ltd.
[0059] The method for testing relative viscosity is as follows: according to GB / T 12006.1-2009 "Plastics Polyamide Part 1: Determination of Viscosity", concentrated sulfuric acid is used as the solvent.
[0060] Example 1
[0061] 20g of polyamide 6 / 66 copolymer solid particles (relative viscosity 2.0) were placed in a four-necked flask, and a polytetrafluoroethylene (PTFE) stirrer was added. The stirring speed was set to 300 rpm, and nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 60 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The solid particles were removed and weighed. The solid particles lost approximately 10 wt% of weight, and crystalline products were observed to precipitate at the outlet bend. The relative viscosity of the solid particles after microwave irradiation was 2.20.
[0062] Comparative Example 1
[0063] Take 20g of polyamide 6 / 66 copolymer solid particles (relative viscosity 2.0), place them in a vacuum oven, and keep them at 120℃ for 15h. The solid particles lose about 10wt% of weight, and the relative viscosity of the solid particles is 2.10.
[0064] Example 2
[0065] 20g of polyamide 6 / 66 copolymer solid particles (relative viscosity 2.0) were placed in a four-necked flask, and a polytetrafluoroethylene (PTFE) stirrer was added. The stirring speed was set to 300 rpm, and nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 120 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The solid particles were removed and weighed; the solid particles lost approximately 10 wt%. Crystalline products were observed to precipitate at the outlet bend. The relative viscosity of the solid particles after microwave irradiation was 2.23.
[0066] Example 3
[0067] 20g of polyamide 6 / 66 copolymer solid particles (relative viscosity 2.0) were placed in a four-necked flask, and a polytetrafluoroethylene (PTFE) stirrer was added. The stirring speed was set to 300 rpm, and nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 20 min), 150–200℃ (heating time 20 min), 200℃ (holding temperature 240 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The solid particles were removed and weighed; the solid particles lost approximately 10 wt%. Crystalline products were observed to precipitate at the outlet bend. The relative viscosity of the solid particles after microwave irradiation was 2.27.
[0068] Example 4
[0069] 20g of polyamide 6 / 66 copolymer solid particles (relative viscosity 2.0) were placed in a four-necked flask, and a polytetrafluoroethylene (PTFE) stirrer was added. The stirring speed was set to 300 rpm, and nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–180℃ (heating time 20 min), 180℃ (holding temperature 360 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The solid particles were removed and weighed; the solid particles lost approximately 10 wt%. Crystalline products were observed to precipitate at the outlet bend. The relative viscosity of the solid particles after microwave irradiation was 2.25.
[0070] Example 5
[0071] 20g of polyamide 6 / 66 copolymer solid particles (relative viscosity 2.0) were placed in a four-necked flask, and a polytetrafluoroethylene (PTFE) stirrer was added. The stirring speed was set to 300 rpm, and nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–190℃ (heating time 25 min), 190℃ (holding temperature 240 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The solid particles were removed and weighed; the solid particles lost approximately 10 wt%. Crystalline products were observed to precipitate at the outlet bend. The relative viscosity of the solid particles after microwave irradiation was 2.23.
[0072] In the following embodiments:
[0073] Maleic anhydride-styrene linear copolymer microspheres were prepared by a self-stabilizing dispersion polymerization method, specifically referring to the published patent CN100579995C. The maleic anhydride-styrene copolymer microspheres were prepared as linear alternating copolymers with an average particle size of 1.1 micrometers.
[0074] Maleic anhydride-isobutylene copolymer microspheres were prepared by a self-stabilizing dispersion polymerization method, specifically referring to the published patent CN116262803A. The maleic anhydride-isobutylene copolymer microspheres are linear alternating copolymers with an average particle size of 1.0 micrometers.
[0075] Maleimide-styrene copolymer microspheres were prepared by the following method: maleic anhydride-styrene linear copolymer microspheres with a particle size of 1.1 μm were placed in a three-necked flask, ammonia gas was introduced, and the reaction was carried out for 0.5 h. The microspheres were then placed in an oven at 180 °C for 3 h. The proportion of imidized anhydride groups was 92%, based on the assumption that the content of all anhydride groups in the maleic anhydride-styrene copolymer was 100%.
[0076] Maleimide-isobutylene copolymer microspheres can be obtained by referring to the preparation method of maleimide-styrene copolymer microspheres.
[0077] Maleic anhydride-styrene copolymer microspheres were prepared by the following method: Maleic anhydride-styrene linear copolymer microspheres with a particle size of 1.1 μm were placed in a three-necked flask, ammonia gas was introduced, and the reaction was carried out for 0.5 h. The microspheres were then removed and dried in an oven at 80 °C for 1 h to prepare amide-modified maleic anhydride-styrene copolymer microspheres (i.e., maleic anhydride copolymer microspheres). The proportion of amidated anhydride groups was 92%, based on the assumption that the content of all anhydride groups in the maleic anhydride-styrene copolymer was 100%.
[0078] Maleamic acid-isobutylene copolymer microspheres can be obtained by referring to the preparation method of maleamic acid-styrene copolymer microspheres.
[0079] Polyamide and polymer microsphere blends are prepared by melt blending polyamide and polymer microspheres at the processing window temperature of polyamide and then pelletizing them.
[0080] Example 6
[0081] Take 20g of a blend of polyamide 6 / 66 copolymer and maleic anhydride-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleic anhydride-isobutylene copolymer microspheres is 100:1), and place the solid particles in a four-necked flask. Add a polytetrafluoroethylene (PTFE) stirrer, set the stirring speed to 300 rpm, purge with nitrogen, insert a temperature sensor into the outer mouth of the flask, and set the microwave extraction program as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (hold for 60 min). Start stirring and run the program. After the program ends, purge with nitrogen until the flask temperature drops to room temperature. The relative viscosity of the solid particles after microwave irradiation is 2.79.
[0082] Example 7
[0083] Take 20g of a blend of polyamide 6 / 66 copolymer and maleic anhydride-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleic anhydride-isobutylene copolymer microspheres is 100:1.5), and place the solid particles in a four-necked flask. Add a polytetrafluoroethylene (PTFE) stirrer, set the stirring speed to 300 rpm, purge with nitrogen, insert a temperature sensor into the outer mouth of the flask, and set the microwave extraction program as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (constant temperature 90 min). Start stirring and run the program. After the program ends, purge with nitrogen until the flask temperature drops to room temperature. The relative viscosity of the solid particles after microwave irradiation is 3.30.
[0084] Example 8
[0085] Take 20g of a blend of polyamide 6 / 66 copolymer and maleamic acid-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleamic acid-isobutylene copolymer microspheres is 100:0.5), and place the solid particles in a four-necked flask. Add a polytetrafluoroethylene (PTFE) stirrer, set the stirring speed to 300 rpm, purge with nitrogen, insert a temperature sensor into the outer mouth of the flask, and set the microwave extraction program as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (hold for 120 min). Start stirring and run the program. After the program ends, purge with nitrogen until the flask temperature drops to room temperature. The relative viscosity of the solid particles after microwave irradiation is 2.51.
[0086] Example 9
[0087] 20g of a blend of polyamide 6 / 66 copolymer (relative viscosity 2.0) and maleic acid-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleic acid-isobutylene copolymer microspheres 100:1) was placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 120 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The relative viscosity of the solid particles after microwave irradiation was 3.01.
[0088] Example 10
[0089] 20g of a blend of polyamide 6 / 66 copolymer (relative viscosity 2.0) and maleic acid-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleic acid-isobutylene copolymer microspheres 100:1.5) was placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 120 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The relative viscosity of the solid particles after microwave irradiation was 3.62.
[0090] Example 11
[0091] 20g of a blend of polyamide 6 / 66 copolymer (relative viscosity 2.0) and maleimide-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleimide-isobutylene copolymer microspheres 100:1) was placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 120 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The relative viscosity of the solid particles after microwave irradiation was 3.13.
[0092] Example 12
[0093] 20g of a blend of polyamide 6 / 66 copolymer (relative viscosity 2.0) and maleimide-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleimide-isobutylene copolymer microspheres 100:1) was placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer neck of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 240 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The relative viscosity of the solid particles after microwave irradiation was 3.14.
[0094] Example 13
[0095] 20g of a blend of polyamide 6 / 66 copolymer (relative viscosity 2.0) and maleimide-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleimide-isobutylene copolymer microspheres 100:1) was placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 480 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The relative viscosity of the solid particles after microwave irradiation was 3.16.
[0096] Example 14
[0097] 20g of a blend of polyamide 6 / 66 copolymer (relative viscosity 2.0) and maleimide-isobutylene copolymer microspheres (mass ratio of polyamide 6 / 66 copolymer to maleimide-isobutylene copolymer microspheres 100:1) was placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 250W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 1440 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The relative viscosity of the solid particles after microwave irradiation was 3.19.
[0098] Example 15
[0099] 20g of polyamide 6 (Hunan Yuehua, YH800) solid particles (relative viscosity 2.8) were placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 350W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (constant temperature 120 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The solid particles were removed and weighed; the solid particles lost approximately 10% of their weight. Crystalline products were observed to precipitate at the outlet bend. The relative viscosity of the solid particles after microwave irradiation was 3.01.
[0100] Example 16
[0101] 20g of a blend of polyamide 6 (Hunan Yuehua, YH800) (relative viscosity 2.8) and maleic anhydride-styrene copolymer microspheres (mass ratio of polyamide 6 to maleic anhydride-styrene copolymer microspheres 100:1) was placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 350W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 120 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The relative viscosity of the solid particles after microwave irradiation was 3.53.
[0102] Example 17
[0103] 20g of a blend of polyamide 6 (Hunan Yuehua, YH800) (relative viscosity 2.8) and maleic acid-styrene copolymer microspheres (mass ratio of polyamide 6 to maleic acid-styrene copolymer microspheres 100:1) was placed in a four-necked flask. A polytetrafluoroethylene (PTFE) stirrer was added, and the stirring speed was set to 300 rpm. Nitrogen gas was introduced for purging. A temperature sensor was inserted into the outer mouth of the flask. The microwave extraction program was set as follows: power 350W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (constant temperature 120 min). Stirring was started and the program was run. After the program ended, nitrogen gas was purged until the flask temperature dropped to room temperature. The relative viscosity of the solid particles after microwave irradiation was 3.71.
[0104] Example 18
[0105] Take 20g of polyamide 6 (Hunan Yuehua, YH800) (relative viscosity 2.8) and maleimide-styrene copolymer blend particles (mass ratio of polyamide 6 to maleimide-styrene copolymer is 100:1), and place the solid particles in a four-necked flask. Add a polytetrafluoroethylene (PTFE) stirrer, set the stirring speed to 300 rpm, purge with nitrogen, insert a temperature sensor into the outer mouth of the flask, and set the microwave extraction instrument program as follows: power 350W, 30–150℃ (heating time 10 min), 150–200℃ (heating time 30 min), 200℃ (holding temperature 120 min). Start stirring and run the program. After the program ends, purge with nitrogen until the flask temperature drops to room temperature. The relative viscosity of the solid particles after microwave irradiation is 3.83.
[0106] As can be seen from Examples and Comparative Example 1, the present invention utilizes microwave irradiation of solid-phase polyamide and optional chain extenders to achieve solid-phase viscosity enhancement of polyamide through a simple method. After microwave irradiation for not less than 30 minutes, the relative viscosity increase of the polyamide is not less than 0.2. In the absence of chain extenders, as shown in Examples 1-5, different times and temperatures have different effects on the viscosity enhancement effect; higher temperatures and longer irradiation times result in better effects.
[0107] A comparison of Examples 6-16 with Examples 1-5 shows that when the chain extender is one of maleic anhydride copolymer microspheres, maleamic acid copolymer, and maleimide copolymer, the microwave irradiation solid-phase polyamide method of the present invention has a better thickening effect. Under the same chain extender dosage, when the chain extender is maleamic acid copolymer and maleimide copolymer, the microwave irradiation solid-phase polyamide method of the present invention has a further better thickening effect; more preferably, when the chain extender is maleimide copolymer, the thickening effect of the microwave irradiation solid-phase polyamide method of the present invention is particularly significant.
[0108] As can be seen from Examples 15-18, for different types of polyamides, such as polyamide 6, the microwave irradiation solid-state polyamide method of the present invention has a similar thickening effect as polyamide 6 / 66.
[0109] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
[0110] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In case of conflict, the definitions in this specification shall prevail.
[0111] When this specification uses the prefixes “known to those skilled in the art,” “prior art,” or similar terms to derive materials, substances, methods, steps, apparatus, or components, the objects derived from such prefixes cover those commonly used in the art at the time of this application, but also include those that are not currently commonly used but will become generally recognized in the art as suitable for similar purposes.
[0112] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values; such ranges or values should be understood to include values close to them. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In principle, various technical solutions can be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.
[0113] In the context of this specification, except where expressly stated otherwise, any matters or issues not mentioned shall apply directly to those known in the art without any modification.
[0114] Furthermore, any implementation described herein can be freely combined with one or more other implementations described herein, and the resulting technical solutions or technical ideas shall be regarded as part of the original disclosure or original record of the present invention, and should not be regarded as new content not disclosed or anticipated herein, unless those skilled in the art believe that the combination is obviously unreasonable.
Claims
1. A method for microwave solid-phase tackifying polyamide, comprising placing a solid-phase polycondensation raw material, including a polyamide and an optional chain extender, in a sealable container, and subjecting the solid-phase polycondensation raw material to microwave irradiation under a protective atmosphere or low-pressure environment and under mixing conditions to obtain the tackifying polyamide; wherein, During microwave irradiation, the solid-phase polycondensation raw material is kept at a temperature between its crystallization temperature and melting temperature for at least 30 minutes.
2. The method according to claim 1, characterized in that: The microwave irradiation comprises three stages: a rapid heating stage, a slow heating stage, and a holding stage; preferably, in the rapid heating stage, the heating rate is 1–50 °C / min, in the slow heating stage, the heating rate is 1–20 °C / min, and in the holding stage, the temperature range is within ±10 °C of a preset value; and / or, The microwave power of the microwave field is 80W to 5000W; and / or, The polyamide is in the form of solid particles or powder; and / or, The protective atmosphere is nitrogen and / or an inert gas; and / or, The low-pressure environment is achieved through a vacuum pump.
3. The method according to claim 1, characterized in that: The polyamide is selected from at least one of polyamide-6, polyamide-66, copolymer of polyamide-6 / polyamide-66, polyamide-1010, polyamide-610, polyamide-612, polyamide-11, polyamide-12, polyamide-46, polyamide-6T, aromatic polyamide, and elastic polyamide.
4. The method according to claim 1, characterized in that: When the solid-phase polycondensation raw material contains a chain extender, the mass ratio of the polyamide to the chain extender is 100:(0.1-20), preferably 100:(0.3-10); and / or, The chain extender is selected from at least one of the following: epoxy functionalized chain extender, oxazoline chain extender, carbonate functionalized chain extender, epoxy chain extender, bicyclic chain extender, isocyanate chain extender, phosphorus-containing chain extender, maleic anhydride copolymer, maleamic acid copolymer, and maleimide copolymer; preferably, the chain extender is selected from at least one of maleamic acid copolymer and maleimide copolymer.
5. The method according to claim 4, characterized in that: The content of acid anhydride in the maleamic acid copolymer and the maleimide copolymer is each no more than 50%, preferably no more than 30%, based on the total molar amount of structural units containing acid anhydride groups, maleamide groups, maleamic acid groups, and maleimide groups as 100%; and / or, The maleamic acid copolymer and the maleimide copolymer are each microspheres, preferably with an average particle size of 0.2 to 100 micrometers.
6. The method according to claim 4, characterized in that: The maleamic acid copolymer and the maleimide copolymer are each derived from the amidation or imideation products of maleic anhydride and its derivative copolymers; preferably, The maleic anhydride and its derivative copolymers are copolymers containing one or more of the structural units of maleic anhydride, maleimide, maleic acid and ammonium salt, and maleamic acid and ammonium salt groups; more preferably, Maleic anhydride and its derivative copolymers are copolymers of polymeric monomers containing one or more of the following groups: maleic anhydride, maleimide, maleic acid and ammonium salt, maleamic acid and ammonium salt, and monomers containing isolated carbon-carbon double bonds.
7. The method according to claim 6, characterized in that: When the maleic anhydride and its derivative copolymers are prepared by amidation, the step of reacting the maleic anhydride and its derivative copolymers with ammonia or ammonia water is included. When preparing the maleiminated copolymer by imidization of maleic anhydride and its derivative copolymers, the process includes reacting maleic anhydride and its derivative copolymers with ammonia or ammonia water, followed by heating to obtain the imidized product.
8. The method according to claim 4, characterized in that: The maleamic acid copolymer and the maleimide copolymer are each products of the amidation or imideation of maleic anhydride copolymers; preferably, The maleic anhydride copolymer is a linear copolymer of maleic anhydride and a monomer containing isolated carbon-carbon double bonds; more preferably, The maleic anhydride copolymer is at least one of a binary copolymer and a ternary copolymer; more preferably, The binary copolymer is a copolymer of maleic anhydride and one or more selected from butene, isobutene, cis-butadiene, pentene, isoprene, cyclopentadiene, dicyclopentadiene, hexene, hexadiene, cyclohexadiene, octene, octadiene, cyclooctadiene, styrene and its derivatives, and vinyl alkyl ethers. More preferably, the molar content of the structural units provided by maleic anhydride in the binary copolymer is 10% to 90%, preferably 20% to 80%, and more preferably 30% to 70%; and / or, More preferably, the terpolymer is a copolymer of maleic anhydride, styrene, and isobutylene. More preferably, the molar content of the structural units provided by maleic anhydride in the terpolymer is 47%-52%, preferably 48%-51%, and the molar ratio of the structural units provided by isobutylene to the structural units provided by styrene is 1:0.2-7.5, more preferably 1:1-5.
9. The method according to claim 8, characterized in that: The maleic anhydride copolymers are linear alternating copolymers; and / or, The maleic anhydride copolymer is a copolymer microsphere, more preferably a copolymer microsphere prepared by a self-stabilizing precipitation polymerization method, wherein the particle size of the copolymer microsphere is 0.2 to 10 micrometers, preferably 0.3 to 3 micrometers, and more preferably 0.4 to 2 micrometers.
10. A product obtained by the method according to any one of claims 1-9.
11. The use of the method of any one of claims 1-9 or the product of claim 10 in solid-phase thickening and articles.
Citation Information
Patent Citations
Copolymerization reaction method for styrene / maleic anhydride
CN100579995C
Method for producing maleimide copolymer, maleimide copolymer, and maleimide composition
CN112574336A
Adhesive comprising copolymer having repeating units of amide group and carboxyl group and / or ammonium salt thereof, and wood-based panel prepared therewith
CN112852356A
Maleic anhydride-isobutylene copolymer microsphere as well as preparation method and application thereof
CN116262803A